2016
DOI: 10.1038/ncomms13260
|View full text |Cite
|
Sign up to set email alerts
|

Photomotility of polymers

Abstract: Light is distinguished as a contactless energy source for microscale devices as it can be directed from remote distances, rapidly turned on or off, spatially modulated across length scales, polarized, or varied in intensity. Motivated in part by these nascent properties of light, transducing photonic stimuli into macroscopic deformation of materials systems has been examined in the last half-century. Here we report photoinduced motion (photomotility) in monolithic polymer films prepared from azobenzene-functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
219
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(221 citation statements)
references
References 30 publications
2
219
0
Order By: Relevance
“…and White et al. have demonstrated motivational milestones such as light‐driven motors, robotic arms, and high‐frequency oscillators . More recently, versatile applications on bio‐inspired and bio‐integrated designs have been presented, including artificial cilia, self‐regulating iris, fluid slugs, as well as inching and swimming robots …”
Section: Polymer Compositions Molecular Weights and Polydispersitymentioning
confidence: 99%
“…and White et al. have demonstrated motivational milestones such as light‐driven motors, robotic arms, and high‐frequency oscillators . More recently, versatile applications on bio‐inspired and bio‐integrated designs have been presented, including artificial cilia, self‐regulating iris, fluid slugs, as well as inching and swimming robots …”
Section: Polymer Compositions Molecular Weights and Polydispersitymentioning
confidence: 99%
“…By employing fluorinated azobenzenes as basic switching elements to slow the thermal re‐conversion from cis back to trans shapes, the fluorinated switches activated by visible light retained their photo‐deformed shape for more than eight days, to build something now approaching ‘real’ light‐powered molecular devices photo‐switches that can now overcome thermal relaxation on a device‐useful timescale. Furthermore, White et al demonstrated photo‐motility of thin strips of azobenzene‐functionalized liquid crystalline polymer networks (azo‐LCNs) . By irradiating these polymer films with broadband UV light they revealed that the both directionality and rate of photo‐motility are highly dependent on the orientation of the liquid crystalline director.…”
Section: Photo‐mechanical Effectsmentioning
confidence: 99%
“…The interplay between intrinsic materials properties and the external stimuli can lead to intriguing phenomena in soft materials, such as self‐oscillation, wave‐like self‐propelling and various forms of self‐sustained motion . Those phenomena are initiated by an in‐built feedback mechanism connecting the material response, stimulus fields, and the structural geometry .…”
mentioning
confidence: 99%